Weaker jobs, weaker innovation: Exploring the temporary employment-product innovation nexus - Armanda Cetrulo; Valeria Cirillo; Dario Guarascio (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2018)
This work explores the relationship between temporary employment and product innovation focusing on five major European economies (France, Germany, Italy, Spain and the Netherlands) observed between 1998 and 2012. Building on the conceptual framework proposed by Kleinknecht et al. (2014), the analysis distinguishes sectors according to their technological characteristics and regimes finding that industries using temporary employment tend to have a weaker product innovation propensity. The negative correlation between temporary employment and innovation is stronger in medium and hightech sectors, identified using both the "Cumulativeness" proxy stemming from Peneder's classification (Peneder, 2010) as well as distinguishing between different Schumpeterian regimes - Schumpeter Mark I vs II - of knowledge accumulation.
Keywords: J40; J63; O31; 330; product innovation; labor market flexibility; temporary employment